The potential effect of applying scaffold hydroxyapatite derived from Portunus pelagicus crab shells on osteonectin and VEGF-B expression - Meinar Nur Ashrin,, Astila Fitriana, Ainy Fitri Nuriyanto, Maretaningtias Dwi Ariani, Michael Josef Kridanto Kamadjaja (Journal of Applied Pharmaceutical Science, 2025)
The excessive resorption of the alveolar bone and the positioning and longevity of implants pose further difficulties for dental professionals. This research was carried out to analyze the VEGF-B and osteonectin expression by applying scaffold Hydroxyapatite (HA) derived from crab shells Portunus Pelagicus in the guinea pigs (Cavia cobaya) sockets following tooth extraction. The methods constituted experimental laboratory research involving two groups: an untreated control group of Cavia cobaya and a Cavia cobaya group to which hydroxyapatite scaffold from crab shells (Portunus pelagicus) was applied, VEGF-B and osteonectin expression being calculated on days 7 and 14 by immunohistochemical staining. ANOVA and Pearson's tests were performed to examine the differentiation between groups and to correlate between those two expressions. HA from Portunus pelagicus crab shells can significantly increase the amount of osteonectin and VEGF-B (p = 0.000) in the treatment group compared to the untreated control group on days 7 and 14. The increases in VEGF-B and osteonectin show a strong mutual correlation (p = 0.87). These findings are significant as they suggest that hydroxyapatite from Portunus pelagicus crab shells can enhance bone healing, providing valuable insights for the development of alternative bone graft materials.
Keywords: Hydroxyapatites, Portunus pelagicus, vascular endothelial growth factor B, osteonectin, bone graft